Absence of vitamin D receptor in mature osteoclasts results in altered osteoclastic activity and bone loss. Issue 177 (March 2018) - Starczak, Yolandi; Reinke, Daniel C.; Barratt, Kate R.; Ryan, Jackson W.; Russell, Patricia K.; Clarke, Michele V.; St-Arnaud, René; Morris, Howard A.; Davey, Rachel A.; Atkins, Gerald J.; Anderson, Paul H.
Highlights: The deletion of vitamin D receptor in osteoclasts results in femoral bone loss. Osteoclast-specific VDRKO mice exhibit a marked reduction in thin trabeculae bone following OVX. Osteoclast-specific VDRKO mice exhibited enhanced expression of osteoclast markers of activity in in vitro cultures. Abstract: Mature osteoclasts express the vitamin D receptor (VDR) and are able to synthesise and respond to 1, 25(OH)2 D3 via CYP27B1 enzyme activity. Whether vitamin D signalling within osteoclasts is necessary for the regulation of osteoclastic bone resorption in an in vivo setting is unclear. To determine the requirement for the VDR- and CYP27B1-mediated activity in mature osteoclasts, conditional deletion mouse models were created whereby either Vdr or Cyp27b1 gene was inactivated by breeding either Vdr fl/fl or Cyp27b1 fl/fl mice with Cathepsin K-Cre transgenic mice (Cstk Cre ) to generate Ctsk Cre /Vdr −/− and Ctsk Cre /Cyp27b1 −/− mice respectively. To account for potential Ctsk Cre -meaited off-target deletion of Vdr, Dmp1 Cre were also used determine the effect of Vdr deletion in osteocytes. Furthermore, Ctsk Cre /Vdr −/− mice were ovariectomised (OVX) to assess the role of VDR in osteoclasts under bone-loss conditions and bone marrow precursor cells were cultured under osteoclastogenic conditions to assess osteoclast formation. Six-week-old Ctsk Cre /Vdr −/− female mice demonstrated a 15% decrease in femoral BV/TV ( p < 0.05). In contrast, BV/TV remained unchanged in Ctsk Cre /Cyp27b1 −/− mice as well as in Dmp1 Cre /VDR −/− mice. When Ctsk Cre /Vdr −/− mice were subjected to OVX, the bone loss that occurred in Ctsk Cre /Vdr −/− was predominantly due to a diminished volume of thinner trabeculae when compared to control levels. These changes in bone volume in Ctsk Cre /Vdr −/− mice occurred without an observable histological change in osteoclast numbers or size. However, while cultured bone marrow-derived osteoclasts from Ctsk Cre /Vdr −/− mice were marginally increased when compared to VDR fl/fl mice, elevated expression of genes such as Cathepsin K, Nfatc1 and VATPase was observed. Collectively, these data indicate that the absence of VDR in mature osteoclasts causes exacerbated bone loss in young mice and during OVX which is associated with enhanced osteoclastic activity and without increased osteoclastogenesis.